Cytokine dynamics in vitiligo: the roles of interleukin-10 and interleukin-17 - Hanan Mohammed Saied (Exploration of Immunology)
Aim: Vitiligo is an autoimmune skin disorder characterized by melanocyte destruction and progressive depigmentation. Cytokine imbalance plays a key role in its pathogenesis. This study aims to evaluate and compare serum levels of the anti-inflammatory cytokine interleukin-10 (IL-10) and the pro-inflammatory cytokine IL-17 in vitiligo patients and healthy individuals, to explore their potential as biomarkers of disease activity. Methods: A total of 60 vitiligo patients and 40 age- and sex-matched healthy controls were recruited. Serum concentrations of IL-10 and IL-17 were measured using enzyme-linked immunosorbent assay (ELISA). Disease severity and duration were also assessed in relation to cytokine levels. Results: Vitiligo patients showed significantly lower IL-10 levels (9.37 ± 0.17 pg/mL) compared to controls (11.38 ± 0.22 pg/mL, P < 0.01), and significantly higher IL-17 levels (326.48 ± 5.49 pg/mL) compared to controls (270.47 ± 8.48 pg/mL, P < 0.01). Conclusions: These findings suggest an inflammatory cytokine imbalance in vitiligo, characterized by decreased IL-10 and elevated IL-17 levels. The significant correlation of IL-17 with disease progression supports its role as a potential biomarker of disease activity. Targeting cytokine pathways may offer new directions for immunomodulatory treatment strategies in vitiligo.